Importance-Performance Analysis Kepuasan Nasabah BritAma Pada Bank BRI Kantor Cabang Pembantu Pasar Natar Lampung Selatan - Arpan, Yunada (Jurnal Manajemen dan Keuangan, 2009)
A qualified and competitive bank is a bank which can support good development BRI is one of national bank in Lampung that has good support to develope financial district suitable with district autonomy procedure. This branch of BRI bank in Natar is the bank which trics to satisfy itâs customers maximumly, especially for the customers who live in Natar, South Lampung.The available data indicate that the quantity of BritAma customers decreased about 36% with the average of decrease 3% per a mouth during the period August 2007 to November 2008. Based on the condition above, the problem formulation of this research is â How is the satisfaction of BritAma cutomers for the service given by the branch of BRI in Natar, South Lampung?.The purpose of this research are:1. To know the satisfactory degree of BritAma customers toward the branch of BRI in Natar, South Lampung.2. To give information about the ways to service the customers better for some companies such as this bank.In connection with the background and the problem formulation this research has the hypothesis below: âThe service given by the branch of BRI in Natar, South Lampung has not given satisfaction to itâs customersâThe result of count of customers satisfaction index is 78,842% this shows that the service given by the branch of BRI in Natar to the customers has not been satisfied. That is reflected by the index is less than 100%. It can be concluded that the hypothesis has been formulated above can be proved with the following count.âThe result of count of Importance Performance Analysis had been done shows that the average which uses the indicator of SERVQUAL about 0,971 is more than the average of customer satisfaction that is 0,745.Keywords: Performance, customers satisfaction, Importance Performance Analysis